Pengaruh Inklusi Keuangan Syariah Terhadap Pembiayaan Industri Kreatif (Studi Kasus KSPPS BMT-NU Jawa Timur Kantor Cabang Lenteng Sumenep) - Istiqamah, Vina Abidatin; Zakik (Universitas Airlangga, 2024)
This study aims to analyze the effect of Islamic financial inclusion on creative industry financing in KSPPS BMT-NU Sumenep. Multiple linear regression analysis technique was applied to identify the influence of independent variables.The research design used in this study is a questionnaire to customers of BMT-NU EAST JAVA Lenteng Branch Office who are willing to be respondents and fill out a questionnaire, the purpose of which is to find out how much influence the independent variables, namely, Profile (X1), Income (X2), Accessibility (X3), and Product (X4) on financing the creative industry in Sumenep Regency. The results of the research obtained through multiple Linear Regression dummy variables are profile variables and products that have a significant positive effect on financing the creative industry of BMT-NU Lenteng Branch Sumenep customers. While the accessibility variable has a significant negative effect on financing the creative industry of BMT-NU Lenteng Sumenep Branch customers. While the income variable has a positive, but insignificant effect on financing the creative idustry of BMT-NU Lenteng Sumenep Branch customers.